Prinsip Pembuktian Sederhana dalam Permohonan Penundaan Kewajiban Pembayaran Utang - Devi Andani; Wiwin Budi Pratiwi (Fakultas Hukum Universitas Islam Indonesia, 2021)
This study aims to determine firstly, the application of simple evidenciary in the application for Postponement of Debt Payment Obligations (PKPU) and secondly, the comparison of the concept of simple evidenciary in PKPU. The research method used is normative legal research, data is collected by means of literature studies and documents written descriptively and analyzed qualitatively. The results of this study show that first, simple evidenciary provision in Article 8 paragraph (4) in conjunction with Article 2 paragraph (1) of the Bankruptcy Law and PKPU, regulates that simple evidenciary applies to applications for bankruptcy statements. Whereas in the PKPU petition, in fact the Bankruptcy Law and PKPU do not require the application of simple evidenciary which states that the petition for a declaration of bankruptcy must be granted if there are facts or circumstances that are simply proven that the requirements for bankruptcy are declared. Second, although the Bankruptcy Law and PKPU do not regulate the principle of simple proof that can be applied in a PKPU application, judges can apply the simple evidenciary principle by taking into account the principles of simple, fast, and low-cost justice and the objectives of the Bankruptcy Law and PKPU can be achieved.